2005
DOI: 10.1120/jacmp.v6i4.2117
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variation in cervical cancer tumor delineation for image‐based radiotherapy planning among and within different specialties

Abstract: Radiation therapy for cervical cancer involves a team of specialists, including diagnostic radiologists (DRs), radiation oncologists (ROs), and medical physicists (MPs), to optimize imaging‐based radiation therapy planning. The purpose of the study was to investigate the interobserver variations in tumor delineation on MR images of cervical cancer within the same and among different specialties. Twenty MRI cervical cancer studies were independently reviewed by two DRs, two ROs, and two MPs. For every study, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…found that collaborative tumour delineation in lung cancer changed contouring in 19/20 cases. Some authors have suggested training with or close collaboration with a radiologist when contouring . The use of multimodality imaging is becoming standard in radiation oncology and attention must be paid to both image registration and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…found that collaborative tumour delineation in lung cancer changed contouring in 19/20 cases. Some authors have suggested training with or close collaboration with a radiologist when contouring . The use of multimodality imaging is becoming standard in radiation oncology and attention must be paid to both image registration and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…First, delineation was conducted by a single radiation oncologist on the MR images with fixed imaging protocols. As several investigators indicated, 24 , 25 these factors may cause the results to change. Second, the margins and coverage were calculated based on the same patient group.…”
Section: Discussionmentioning
confidence: 99%
“…In MR-GTV, the uncertainties include the following: partial voluming by parametrial fat, extension of the tumor into parametrial space, similar signal intensity of structures proximal to the tumor, susceptibility artifacts from bowels and vaginal tampons, as well as presence of atypical myoma. 29 The present study attempted to minimize these ambiguities by consulting an experienced radiologist and a radiation oncologist to determine the MR-GTV. All images were reviewed with knowledge of the patient's clinical history and results of previous imaging studies at the time of localization, thus minimizing MR-GTV measurement errors.…”
Section: Discussionmentioning
confidence: 99%